Penyuntingan Teks Digital Manuskrip Pesantren sebagai Upaya Pelestarian Warisan Intelektual Islam Nusantara - Sehid Sehid; Farisi Farisi; Muhammad Zaironi; M. Ilham Firmansyah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study discusses the editing of digital texts of pesantren manuscripts as an effort to preserve the Islamic intellectual heritage of the Indonesian archipelago, a heritage of considerable historical, cultural, and academic value. Pesantren manuscripts are largely written in Arabic, Pegon, and Jawi scripts on aging paper media, so many of them are physically fragile, with faded ink and torn or illegible pages, making systematic digital editing an urgent scholarly task. Using a descriptive qualitative approach within a digital-philology framework, data were collected through participant observation, in-depth interviews, and documentation study, and were analyzed through description of the manuscript, textual criticism, transcription, and text editing, with validity secured through source, technique, and time triangulation as well as member checking. The findings show that the editing process comprises manuscript inventory and description, digitization, transliteration and transcription from Arabic-Malay/Pegon script into Latin script, textual criticism, language and spelling editing, structural organization, technical editing, and verification/validation, so that the resulting text becomes clearer, easier to read, and remains authentic to the source. The study further emphasizes fidelity to the original manuscript, careful recording of textual variants and marginal notes, and verification of Qur'anic, hadith, and scholarly references to safeguard scholarly validity. Thus, digital editing of pesantren manuscripts is not merely a technical task but also a strategy for preserving scholarly tradition and the historical identity of the pesantren for future generations.